Evaluation of damp‐heat testing of photovoltaic modules. (16th November 2016) - Koehl, Michael; Hoffmann, Stephan; Wiesmeier, Stefan
Abstract: Temperature, temperature cycling, moisture, ultraviolet radiation, and negative bias voltage are considered as main degradation factors for photovoltaic modules by causing hydrolysis and photo‐degradation of polymeric components, corrosion of glass, and of metallic components like grids and interconnectors. Commercially produced photovoltaic modules with crystalline silicon cells were exposed to accelerated damp‐heat testing in the lab. Test temperatures were 75, 85, and 90 °C. The tests were continued until a final degradation state was reached (3500–7000 h). The degradation function could be modeled by a Boltzmann function allowing the determination of the time to failure (20% power loss). The time to failure as function of the test temperature follows Arrhenius relations allowing the evaluation of the activation energy of the dominating degradation process. These time‐transformation functions could be used for service life estimation. Electroluminescence pictures illustrate the degradation behavior and the differences of the modules, indicating no changes in the degradation mechanisms for the different temperatures. A procedure for the evaluation of outdoor operation conditions towards accelerated service life testing with respect to moisture impact is proposed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Normalized module power during damp‐heat testing at different temperatures can be modeled and used for evaluation of the time‐transformation function for service life estimation.